Sistem Monitoring Slot Parkir Berbasis Esp32 Menggunakan Sensor Ultrasonik Dengan Web Dashboard Iot - luluk, syeril; Sujono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Insufficient parking capacity and the absence of real-time information regarding slot availability remain persistent issues in public facilities such as campuses, shopping centers, and office buildings. These conditions contribute to traffic congestion, time inefficiency, and suboptimal parking management. An automated and accurate monitoring system is required to provide immediate information for both parking administrators and vehicle users. This research aims to design and implement a parking slot monitoring system based on the ESP32 microcontroller using ultrasonic sensors to detect vehicle presence. The system is integrated with an Internet of Things (IoT) dashboard, allowing parking availability to be monitored through an internet connection. The methodology includes hardware design, software development, IoT integration, and functional as well as sensor accuracy testing. Each parking slot is equipped with an ultrasonic sensor to measure the distance between the sensor and the object positioned in front of it. Distance data are processed by the ESP32 to determine whether a slot is occupied or vacant. The processed data are transmitted to an IoT server via Wi-Fi and displayed on a dashboard in a structured visual format. Experimental results demonstrate that the system operates according to design specifications and provides real-time parking availability information with reliable detection accuracy. The proposed system supports more efficient parking management and accelerates the process of locating vacant slots.